Strategi Pemasaran dan Pembentukan Keputusan Pembelian Konsumen: Studi Kasus Produk Wardah Pada Beauty Store Lokal - Deria Ayuningtyas; Mourris Sagara; Eni Afni Jalilah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This study aims to analyze marketing strategies and their role in influencing consumer purchasing decisions for Wardah products in local beauty stores. The research employed a qualitative descriptive approach to gain an in-depth understanding of consumer perceptions and experiences related to marketing practices. Data were collected through interviews with consumers and store personnel, direct observation of marketing activities at the point of sale, and documentation of promotional materials. The analysis focused on the implementation of key marketing strategy elements, including product quality, pricing policies, promotional activities, and distribution channels, as well as how these elements are perceived and interpreted by consumers during the purchasing decision-making process. The findings indicate that the implemented marketing strategies play an important role in shaping brand awareness, consumer preferences, and confidence in Wardah products. However, their influence on purchasing decisions is not singular or deterministic, as consumers’ choices are also affected by prior usage experiences, personal needs, and subjective considerations. Overall, this study emphasizes the importance of adopting a process-oriented approach to understanding consumer purchasing decisions within the context of local cosmetic retail.